Scribbles and Ink : out of the box - Long, Ethan (Jump into chapters book., 2014)
Scribbles the cat and Ink the mouse are friends and fellow artists, but when Ink receives a box of cheese they squabble over who will get to make something from the box until Scribbles finds a solution.